Discovery of multiple interacting partners of gankyrin, a proteasomal chaperone and an oncoprotein—Evidence for a common hot spot site at the interface and its functional relevance. Issue 7 (15th January 2014) - Nanaware, Padma P.; Ramteke, Manoj P.; Somavarapu, Arun K.; Venkatraman, Prasanna
ABSTRACT Gankyrin, a non‐ATPase component of the proteasome and a chaperone of proteasome assembly, is also an oncoprotein. Gankyrin regulates a variety of oncogenic signaling pathways in cancer cells and accelerates degradation of tumor suppressor proteins p53 and Rb. Therefore gankyrin may be a unique hub integrating signaling networks with the degradation pathway. To identify new interactions that may be crucial in consolidating its role as an oncogenic hub, crystal structure of gankyrin‐proteasome ATPase complex was used to predict novel interacting partners. EEVD, a four amino acid linear sequence seems a hot spot site at this interface. By searching for EEVD in exposed regions of human proteins in PDB database, we predicted 34 novel interactions. Eight proteins were tested and seven of them were found to interact with gankyrin. Affinity of four interactions is high enough for endogenous detection. Others require gankyrin overexpression in HEK 293 cells or occur endogenously in breast cancer cell line‐ MDA‐MB‐435, reflecting lower affinity or presence of a deregulated network. Mutagenesis and peptide inhibition confirm that EEVD is the common hot spot site at these interfaces and therefore a potential polypharmacological drug target. In MDA‐MB‐231 cells in which the endogenous CLIC1 is silenced, trans‐expression of Wt protein (CLIC1_EEVD) and not the hot spot site mutant (CLIC1_AAVA) resulted in significant rescue of the migratory potential. Our approach can be extended to identify novel functionally relevant protein‐protein interactions, in expansion of oncogenic networks and in identifying potential therapeutic targets. Proteins 2014; 82:1283–1300. © 2013 Wiley Periodicals, Inc.